Factors Associated with the lack of use of Contraceptive Methods in Female Adolescent in Peru Endes 2018-2020: Factores asociados al no uso de métodos anticonceptivos en mujeres adolescentes del Perú. ENDES 2018-2020 - Dulanto-Ramos, Yolanda B. (2022)
Introduction: In Peru, adolescents tend to use contraceptive methods (CM) less frequently, constituting a subgroup at risk of unwanted pregnancies and sexually transmitted diseases. Methods: Quantitative, observational, analytical-cross-sectional study corresponding to a secondary analysis of data from women aged 15 to 19 from the ENDES 2018-2020. To quantify the association, Poisson regression was used for robust variances, calculating the Prevalence Ratio (PR) in its crude (PRc) and adjusted (PRa) forms, with a 95% confidence interval. Results: 28.4% did not use MC, there was a significant association for the variables without a partner (Rpa: 2.49 CI: 1.99-3.11) and zero children (Rpa: 2.73 CI: 2.22-3 .35). Conclusions: The factors associated with the lack of CM in female adolescents were without a partner and zero children, with a higher prevalence of the lack of CM.